A comparative study of grain and some morpho-physiological characters in six varieties of rice - Yap, Thoo Chai; Lai, Sin Siang; Poh, Chip Teck (Faculty of Agriculture, University of Malaya, 1973)
Six varieties of rice were grown in pots and their growth and rate of leaf senescence, rate of grain filling, grain yield and some morpho-physiological characters were examined. The results indicated that the increase of grain weight occurred only in first three weeks after anthesis. High yielders were characterized by a larger functional green leaf area whose peak coincided with the date of anthesis. The flag leaf area of a rice plant may be the best indicator for these desirable characteristics.